Developing SPOK Litaracy Board Media (PALIPOK) for Reading of First Grade of Elementary School - Novita, Zhella Rahma; Regina, Belinda Dewi; Ulum, Bahrul (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
Based on the results of observations, namely by knowing the conditions in the field with a total number of students, namely 13 students, the learning media is said to have not trained students' reading skills and students have not experienced, still have difficulty in carrying out learning. For that we need media that can support students' reading skills in learning activities. This study uses the ADDIE model with five stages, namely: analysis, design, development, implementation, and evaluation. The results of the evaluation through the material expert validation test stage 1 were 72.72 in stage 2 of 86.36, while the media validation test was 73.07, the teacher's response was 65.62 and the results of student responses from 13 students who did not enter 2 were 72, 10. This falls into the good category and is good to use as the basis for a conversion table. The results of these efforts indicate that the media is in the appropriate category for use.